2018
DOI: 10.1007/s00401-018-1846-7
|View full text |Cite
|
Sign up to set email alerts
|

Diffusible, highly bioactive oligomers represent a critical minority of soluble Aβ in Alzheimer’s disease brain

Abstract: Significant data suggest that soluble Aβ oligomers play an important role in Alzheimer's disease (AD), but there is great confusion over what exactly constitutes an Aβ oligomer and which oligomers are toxic. Most studies have utilized synthetic Aβ peptides, but the relevance of these test tube experiments to the conditions that prevail in AD is uncertain. A few groups have studied Aβ extracted from human brain, but they employed vigorous tissue homogenization which is likely to release insoluble Aβ that was se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
141
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 113 publications
(148 citation statements)
references
References 64 publications
(124 reference statements)
7
141
0
Order By: Relevance
“…The YZ1 iPSC line [95] was used to prepare neurogenin 2 (Ngn2)-induced human neurons [96] as described previously [41,45]. On iN day 4, cells were plated at 4000 cells/ well on Matrigel (Corning Life Sciences, Corning, NY)coated plates (#655090; Greiner Bio-One, Monroe, NC) and maintained until iN day 21, a time point when iNs are fully mature (Supplementary Figure 5A).…”
Section: Production Of Induced Neurons (Ins) From Human Induced Plurimentioning
confidence: 99%
See 1 more Smart Citation
“…The YZ1 iPSC line [95] was used to prepare neurogenin 2 (Ngn2)-induced human neurons [96] as described previously [41,45]. On iN day 4, cells were plated at 4000 cells/ well on Matrigel (Corning Life Sciences, Corning, NY)coated plates (#655090; Greiner Bio-One, Monroe, NC) and maintained until iN day 21, a time point when iNs are fully mature (Supplementary Figure 5A).…”
Section: Production Of Induced Neurons (Ins) From Human Induced Plurimentioning
confidence: 99%
“…Given the pleomorphic nature of Aβ assemblies formed in vitro [89] and those in extracts of human brain [25,41,92], it is reasonable to expect that toxicity is mediated by more than one Aβ assembly and that this could involve interactions between specific Aβ assemblies and specific receptors, such as PrP C and rather non-specific membrane perturbations [87]. PrP C is a membrane-associated protein best known for its role in transmissible spongiform encephalopathies [71].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, other work indicates that the large oligomer Aβ*56 induces specific changes in neuronal signaling leading to tau phosphorylation and aggregation, whereas dimers and trimers do not . Recent studies have shown that most Aβ extracted from AD brain is innocuous and only some species cause neurotoxicity . This suggests that generic antioligomer therapies, including Aβ antibodies, may be largely bound by the extensive pool of inactive oligomers, whereas targeting the small pool of diffusible, bioactive Aβ may be more useful.…”
Section: Evolution Of the Amyloid Cascade Hypothesismentioning
confidence: 99%
“…While Aβ aggregation is widely acknowledged to be central to AD pathogenesis, an increasing body of evidence indicates that only a sub-population of Aβ aggregates are bioactive (Brinkmalm et al, 2018;Hong et al, 2018;Lesne, 2013). As with PrP and prion disease Sandberg et al, 2011;Sandberg et al, 2014), the form or forms of Aβ which mediate toxicity are not yet defined.…”
Section: Discussionmentioning
confidence: 99%